Aplicações de álgebra linear - D`Agostin, Izabele (2020)
This work presents several applications involving Linear Algebra. Among them, the Lights Out game which can be used as a way to provide a context of some issues in higher education. In order to accomplish this, we intruduce and analyze the main concepts associated with matrices, determinants, linear systems, congruencies and vector spaces. Finally, we propose an activity focused on high school students that involves the use of mathematical modelling to arrive at the resolution of linear systems and matrix multiplication.